Pengaruh Pemahaman, Sanksi Perpajakan, Tingkat Kepercayaan Kepada Pemerintah Dan Hukum Terhadap Kepatuhan Wajib Pajak Dalam Membayar PBB-P2 Kabupaten Karawang - Saputra, Muhamad Taufik Arya; Yanti, Yanti; Lasmini, Lilis (Peneliti.net, 2023)
This discussion study was conducted in order to determine the effect of understanding, Tax sanctions, and the level of trust in the government and the law on taxpayer compliance in paying land tax and rural urban buildings in Karawang Regency. The Total sample used in this discussion study is 100 respondents calculated using simple random sampling method. Data collection conducted in the study of this discussion through the questionnaire method. The method of data analysis conducted to process the data in this discussion study using PLS with Smart PLS 3.0 software. The results of the analysis showed that understanding, Tax sanctions, the level of trust in the government and the law affect the compliance of taxpayers in paying land tax and rural urban buildings.